UNDERSTANDING OF ECOTOURISM IN KAMPUNG PATIN VILLAGE, KAMPAR REGENCY, AS A BIOLOGY LEARNING FOR STUDENTS OF SMA NEGERI 2 XIII KOTO KAMPAR - Sukma RA, Dodi; Hadinoto, Hadinoto; Akbar, Muhammad Azhari (Universitas Lancang Kuning, 2024)
Learning about ecotourism is essential as it promotes environmental awareness, fosters sustainable practices, and empowers communities to protect natural and cultural resources for future generations. This study aims to explore the understanding of ecotourism in Kampung Patin Village, Kampar Regency, as a biology learning medium for students of SMA Negeri 2 XIII Koto Kampar. The study adopts a descriptive quantitative approach, using questionnaires, interviews, and observations to collect data from 30 students in grade XII who participated in a field trip to Kampung Patin. The findings indicate that the students have a good understanding of the ecotourism concepts observed in the village, with an average score of 80.5%. Students demonstrated strong comprehension of ecosystem concepts (85%), environmental awareness (78%), and the benefits of ecotourism-based learning (79%). The field trip activities, including ecosystem observation, identification of local biodiversity, and discussions about environmental impacts, were highly engaging and effective in enhancing students' learning experiences. The results suggest that Kampung Patin Village is a valuable resource for biology education, providing a contextual and interactive learning environment that promotes both cognitive and affective development. The study concludes that integrating ecotourism into biology education offers a promising approach to improve students' understanding of biological concepts and environmental conservation.